2012
DOI: 10.2166/wst.2012.767
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium, kinetic and thermodynamic studies of mercury adsorption on almond shell

Abstract: The application of almond shell as a low cost natural adsorbent to remove Hg(2+) from aqueous solution was investigated. Batch experiments were carried out to evaluate the adsorption capacity of the material. The chemical and physical parameters such as pH, sorbent amount, initial ion concentration, and contact time were optimized for the maximum uptake of mercury onto the solid surface. Adsorption isotherms were expressed by Langmuir and Freundlich adsorption models, and the experimental data were found to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…The positive value of Δ S ° reflected an increased degree of randomness at the solid/liquid interface during adsorption of all the three contaminants. Similar type of observations have been made during adsorption studies of MB , TNT , and Hg (II) by different researchers.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The positive value of Δ S ° reflected an increased degree of randomness at the solid/liquid interface during adsorption of all the three contaminants. Similar type of observations have been made during adsorption studies of MB , TNT , and Hg (II) by different researchers.…”
Section: Resultssupporting
confidence: 85%
“…However, the linear plot of t / q t versus t evidently showed that the experimental results and the calculated values of q e (Table ) obtained by the pseudo‐second‐order kinetic model were comparable [Supporting Information, Figure S8(b)]. The values of R 2 (0.998–0.999) calculated from the pseudo‐second‐order‐kinetic model were relatively higher than those for the pseudo‐first‐order model (0.828–0.994), indicating that the pseudo‐second‐order adsorption mechanism was dominant in the adsorption process of Hg (II) on Co/SiO 2 .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The obtained residues were dissolved in 20 mL of bi-distilled water and filtrated by filter paper. The filtrate was diluted by 50 mL of bi-distilled water (Khaloo et al 2012). Aliquots of the solution were introduced to the proposed methodology for Cd(II) investigation.…”
Section: Samples Analysismentioning
confidence: 99%
“…107,108 Moreover, the use of agricultural products and by-products has been widely investigated as a replacement for current adsorbents for removing mercury and mercury compounds from gas, water, and wastewater. 109 Also, the best available adsorption technologies to control mercury emission will be considered by the performance and cost. Therefore, advanced adsorption technology and adsorption behavior on mercury will be developed by economic and environmental evaluations for the adsorbents with additives to prevent mercury release into the atmosphere.…”
Section: Future Trends In Mercury Control Technologiesmentioning
confidence: 99%